2007
DOI: 10.1086/510842
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Helium Abundance as a Function of Speed and Heliographic Latitude: Variation through a Solar Cycle

Abstract: We present a study of the variation of the relative abundance of helium to hydrogen in the solar wind as a function of solar wind speed and heliographic latitude over the previous solar cycle. The average values of A He , the ratio of helium to hydrogen number densities, are calculated in 25 speed intervals over ($27 day) Carrington rotations using Faraday cup observations from the Wind spacecraft between 1995 and 2005. We find that for solar wind speeds between 350 and 415 km s À1 , A He varies with a clear 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
223
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(253 citation statements)
references
References 36 publications
22
223
1
Order By: Relevance
“…Labels indicate the velocity bin in km/s corresponding to the data points. The ordering of the helium abundances according to velocities corresponds to expectations for a Coulomb drag model, and long-range averages of He/H abundance ratios observed by Aellig et al (2001) and by Kasper et al (2007). The large scatter of data points in the higher velocity bins could possibly be caused by an admixture of CME-ejecta.…”
Section: H I Given Insupporting
confidence: 71%
See 1 more Smart Citation
“…Labels indicate the velocity bin in km/s corresponding to the data points. The ordering of the helium abundances according to velocities corresponds to expectations for a Coulomb drag model, and long-range averages of He/H abundance ratios observed by Aellig et al (2001) and by Kasper et al (2007). The large scatter of data points in the higher velocity bins could possibly be caused by an admixture of CME-ejecta.…”
Section: H I Given Insupporting
confidence: 71%
“…Substantial observational evidence indicates that this mechanism operates in the context of variably diverging open magnetic flux tubes (see Kasper et al 2007, for a more extensive discussion).…”
Section: Coulomb Drag Versus Fip-effectmentioning
confidence: 99%
“…Finally, when |δv αp | > δv c αp , strong heating is restricted to the high energy tail of the He 2+ VDF. By virtue of the fact that H + far outnumbers He 2+ [34], the H + will absorb the majority of the wave power in this regime. T ⊥α /T ⊥p will be lower still in this regime, while T ⊥p /T p will be elevated as the H + ions experience cyclotron resonant heating.…”
Section: For δV Cmentioning
confidence: 99%
“…We followed previously documented procedures to select the subset of measurements for this study [34]. That work also examined solar wind conditions as a function of the Coulomb collision frequency.…”
Section: For δV Cmentioning
confidence: 99%
“…In the second column typical slow solar wind values are shown for comparison. As /p abundance varies as a function of solar wind velocity and solar cycle (Kasper et al 2007 and references therein), we use the observed coronal value of 4% for comparison. In the third column are the averages for each parameter for all large flare associated events.…”
Section: Icme Parameter Dependence On Source Longitude and Associatedmentioning
confidence: 99%